DSP controlled low-voltage high-current fast-transient voltage regulator module - Kasparis, Takis; Abu-Qahouq, Jaber A.; Pongratananukul, Nattorn (My University, 2002)
Future generation of microprocessors will require high performance Voltage Regulator Modules (VRMs) that produce tightly regulated low supply voltage with very small deviation window and able to respond very quickly to a large and continuous load transients at high output current while maintaining a high power density. On one hand, the current drawn from the VRM by the microprocessor is continuously changing since it depends at the current use of the microprocessor. On the other hand, High Frequency VRMs as any Power Electronics System is a complex combination of linear, nonlinear, and switching elements that is required to have fast dynamics. Moreover, this complex combination is also real-time system that needs to continuously and instantly monitor and respond to the load changes (the microprocessor). A high performance basic control loop is essential to follow up with such transients. Such controller design is usually complicated especially since it requires high knowledge of the converter and its behavior and accurate converter model that includes nonlinearities and parameters and components variations. DSP has many advantages over the analog circuits when it comes to applying high performance sophisticated control techniques such the simplicity in applying sophisticated control algorithms and modifying them via software revision, lower environmental and noise sensitivity, and less components count.
Keywords: Algorithms; Voltage regulators; Power electronics; Microprocessors